Investigating the Translanguaging in South African Higher Education: Insights from Lecturers and Students - Dorcas Cathrine Mokgope; Rapeta, Seshoka Joseph (Yayasan Nurul Yakin Bunga Tanjung, 2025)
This study aims to investigate how translanguaging is practiced by both lecturers and students in South African higher education institutions, to benefit both teaching and learning processes. A qualitative case study research design was employed for this study, as it offers a comprehensive and in-depth exploration of complex phenomena within their real-life context. Six lecturers and six students from a North-West Technical and Vocational Education and Training (TVET) college in South Africa participated in this study through semi-structured interviews. Thematic data analysis was employed to interpret and make sense of the collected data. The findings revealed that translanguaging creates inclusive educational spaces where linguistic and cultural diversity are valued, supports the construction of social connections among learners from diverse backgrounds, and enables students to understand academic content more effectively and express it more clearly. These findings suggest that the use of English as a medium of instruction and its impact on teaching and learning can be a valuable framework for multilingual contexts, as it empowers learners to use their home language. It is recommended that clear language policies be developed that recognise and support translanguaging as a legitimate pedagogical strategy.